IN VITRO ANTIBACTERIAL POTENTIAL OF DIFFERENT COMBINATION OF PLANT EXTRACT OF SOME COMMON WEED PLANTS AGAINST XANTHOMONAS ORYZAE AND AGROBACTERIUM SPP - Saha, Tanushri; Modi, Suchi (International Journal of Research -GRANTHAALAYAH, 2025)
The present study investigates the antibacterial activity of various polyherbal combinations against two significant plant pathogens, Xanthomonas oryzae (ATCC 35933) and Agrobacterium spp. (ATCC 12210), both of which are known to cause major crop losses. Using the agar well diffusion method, five different polyherbal combinations (F-1 to F-5) were evaluated at a concentration of 100 mg/ml. The results showed a progressive increase in antibacterial activity from F-1 to F-5, with F-5 exhibiting the largest zones of inhibition—21 mm against X. oryzae and 25 mm against Agrobacterium spp. This enhanced activity is attributed to the synergistic action of phytochemicals within the polyherbal mix. The findings highlight the potential of polyherbal combinations as eco-friendly biopesticides and suggest that such natural alternatives could play a significant role in sustainable agricultural practices. Further studies are recommended to validate these results under field conditions and optimize formulations for commercial use.